Management of massive hemothorax due to internal mammary pseudoaneurysm treated with angioembolization post-cesarean section involving traumatic fetal extraction: A case report - Bruna Mohr Franciosi; Eduardo Zanotta Rodrigues; Israel Dumont Pedroso de Oliveira; Maria Fernanda Oliva Detanico (Trauma Case Reports)
Introduction: Pseudoaneurysm, or false aneurysm, is a clinical entity caused by rupture of the arterial wall, leading to blood leakage that is confined by sorroundig tissue. Massive hemothorax constitutes a life-threatening condition demanding timely and accurate medical response. Case report: A puerperal presented with a massive hemothorax precipitated by a traumatic cesarean section due to hemorrhage from a pseudoaneurysm of the left internal thoracic artery. Initial treatment involved a sternotomy, followed by a conclusive therapy via angioembolization. Conclusion: Precise assessment, including the measurement and localization of the ITA pseudoaneurysm is crucial to formulate an appropriate therapeutic strategy. Current medial practice favors endovascular embolization as a reliable and minimally invasive alternative to open surgery, establishing ir as the treatment of choice.